A retrospective comparative study of the efficacy and safety of two regimens of diphenylcyclopropenone in the treatment of recalcitrant alopecia areata - Tueboon Sriphojanart; Saranya Khunkhet; Poonkiat Suchonwanit (PAGEPress Publications, 2017)
Diphenylcyclopropenone (DPCP) is an effective topical immunotherapy for recalcitrant alopecia areata (AA), which sometimes requires prolonged treatment. We developed a new treatment protocol to shorten the duration of therapy. This study aimed to compare the efficacy and safety of the new treatment protocol with the standard treatment protocol in the treatment of recalcitrant AA. We conducted a 6-year retrospective comparative study of patients with AA who received one of the DPCP treatment protocols at our institute. Patients' information was collected and subsequent statistically analyzed. Thirtynine patients (16 in the new treatment group and 23 in the standard treatment group) were included. There were no statistically significant differences in area of hair regrowth. Mean duration to initial hair regrowth and mean duration to significant hair regrowth in the new treatment group were significantly shorter than in the standard treatment group (P=0.002 and 0.01, respectively). Adverse effects were slightly higher in the new treatment group. The present study reveals the effectiveness and safety of the new treatment protocol, which shortens the duration of DPCP treatment and could represent an alternative regimen.